Muda-Mudi-Madu, Young Marriage Trend, Career Women, and the Perception of Polygamy in the Interpretation of Al-Mishbah - Amanu, Masykur; Rhain, Muh. Ainur (Universitas Muhammadiyah Surakarta, 2023)
The problems of young people are often associated with the problem of marriage or life partners. Among them, some are motivated to marry young, and some choose to pursue a career, so perhaps this discussion can be related to polygamy. There are many reasons behind these desires, especially with the increasingly developing era often giving rise to new problems that still lack solutions. In Islam, someone who has reached the age of puberty is highly recommended to get married. In Java itself, those who delay their marriage often get a bad social status or even get ostracized, which, in fact, is an encouragement for someone to seriously prepare for marriage. From several studies conducted by Prof. Dr. Quraish Shihab in his Tafsir book, he describes that every problem has a subjective and objective background according to the perspective of the Shari'a. He does not agree with the phenomenon of young marriage if the excuse is only to avoid adultery, arguing that age maturity is a priority consideration in a person's readiness to face household polemics. Likewise, serious career pursuit, which often dissuades someone from following the Prophet's sunnah, will be bad if it invites more dangerous consequences. As for the opinion he expressed regarding polygamy, he followed the opinion of the majority of ulama regarding the permissibility of polygamy and clearly forbade polyandry. The purpose of marriage and its consequences are so complex, so what needs to be paid attention to is education and the maturation of the individual's thinking power to realize the purpose of marriage.